2022
DOI: 10.1080/10447318.2022.2088451
|View full text |Cite
|
Sign up to set email alerts
|

Creativity and Smartphone Use: Three Correlational Studies

Abstract: Various books and popular media outlets claim that mindless smartphone use can impair creativity, yet few studies have tested this idea. We conducted a survey and three correlational studies focused on divergent thinking, the mindful ability to generate creative responses to open-ended problems. Most of the 48, 000 participants surveyed thought that smartphone use reduced creativity. This view was consistent with the negative correlations we found between divergent thinking and both screen time and problematic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…However, when people use mobile phones to design interactions and share information, they may generate positive new ideas that enhance creativity (Marty-Dugas et al, 2018). The findings suggest a weak correlation between mobile phone use and creative ideation, which is in line with the results of a previous study (Olson et al, 2023). The findings also suggest that mobile phone use does not necessarily have negative effects.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, when people use mobile phones to design interactions and share information, they may generate positive new ideas that enhance creativity (Marty-Dugas et al, 2018). The findings suggest a weak correlation between mobile phone use and creative ideation, which is in line with the results of a previous study (Olson et al, 2023). The findings also suggest that mobile phone use does not necessarily have negative effects.…”
Section: Discussionsupporting
confidence: 91%
“…Whereas some researches have shown no correlation between smartphone addiction and creative achievement (Upshaw et al, 2022) or divergent and convergent thinking (Linares & Sellier, 2021; Olson et al, 2023; Rodríguez et al, 2020), other studies have demonstrated that the use of smartphones correlates positively with mind-wandering (Marty-Dugas et al, 2018; Müller et al, 2021), which is considered a correlate of creativity (Agnoli et al, 2018). These findings suggest that the relationship between mobile phone use and creative ideation remains to be fully elucidated.…”
Section: Mobile Phone Use and Creative Ideationmentioning
confidence: 99%
“…One third of the sample was analysed to test an unrelated hypothesis (cf. Study 3 inOlson, Sandra, Langer, et al, 2022).…”
mentioning
confidence: 99%
“…In the long term, smartphone overuse and compulsive use reduce concentration abilities, wellbeing and creativity [18,19]. The massive use of smartphones could affect cognitive functions and influence performance, especially in learning contexts, such as schools [20][21][22], and in the professional field [22,23].…”
Section: Smartphone Distractionmentioning
confidence: 99%